Beyond the "Repressive Hypothesis": "Subject-" and "Libido-Effect" in Althusser. Issue 3 (3rd July 2019) - Morfino, Vittorio; Pippa, Stefano
Abstract : The essay "Ideology and Ideological State Apparatuses" (ISAs) contains a famous statement about ideology in relation to the psychoanalytic problematic: namely, that "ideology is eternal, exactly like the unconscious." However, Althusser does not offer any further clarification on this parallelism. Further, in a letter from the late 1970s, he states that he has "stopped short … before the question … about the 'relations' between ideology (or concrete ideological formations) and the unconscious." But in a text that precedes the ISA essay, "Three Notes on the Theory of Discourses, " published posthumously, Althusser tried to develop exactly a theory of the articulation of the ideological and of the unconscious, using a new set of concepts. In this text he combined systematically and for the first time what, borrowing a term from Balibar, could be called an "ontology of relations, " with the categories of the "encounter" and "taking hold."